Strategi Pembelajaran dalam Mengembangkan Keterampilan Membaca dan Menulis Bagi Anak Tunagrahita - Zuhria, Ifati; Ghany Hayudinna, Hafizah (Indonesian Journal of Islamic Elementary Education, 2021)
Learning strategy is a plan of learning activities in order to create effective and efficient learning activities to achieve learning objectives. The strategy used by the teacher is an important thing that can deal with the lack of abilities possessed by mentally retarded children. Mentally retarded children are children who have an IQ below the average. The purpose of this study was to describe the learning strategies used in developing reading and writing skills and to analyze the supporting and inhibiting factors in developing the reading and writing skills of mentally retarded children. The method in this study usedqualitative research. The process of data collection was carried out using interviews and documentation. In developing the reading and writing skills of mentally retarded children, the teacher makes lesson plans and short-term plans. The learning strategies used by the teacher include direct learning strategies and contextual learning strategies. The learning method used is the lecture method, the exercise method and the task method. The learning media used are letter cards and pictures. The learning evaluation used is a check list and a written test. Supporting factors in developing reading and writing skills for mentally retarded children include factors from the teacher, habituation, and parental participation. The inhibiting factors are the ability of students and the lack of parental participation.